A case of ectopic pancreas in the ileum presenting as obscure gastrointestinal bleeding and abdominal pain - Mickuniene, Rugile (BMC Gastroenterol, 2019)
BACKGROUND: Ectopic pancreas is an infrequent submucosal tumor in the gastrointestinal tract defined as a pancreatic tissue lacking vascular or anatomic continuity with the main body of the pancreas. Ectopic pancreas in the ileum is a rare and often an incidental finding. We report a case of ectopic pancreas in the ileum causing obscure gastrointestinal bleeding and episodes of abdominal pain. CASE PRESENTATION: 59-year-old man with 3 months history of intermittent melena, accompanied by the episodes of abdominal pain in the left upper quadrant and generalized fatigue was admitted to our department. The investigations showed that the patient had a low hemoglobin level, i.e. 10.9 g/dL with hypochromic microcytic anemia pattern seen in complete blood count (MCV 70.2 fl, MCH 21.4 pg). Esophagogastroduodenoscopy and colonoscopy did not reveal any abnormalities. Magnetic resonance enterography revealed a large (2.5 × 2.3 cm) pedunculated polyp in the ileum. Examination by single-balloon enteroscopy revealed a polyp with long pedicle located approximately 1.5 m distal to terminal ileum. Polypectomy was performed. Histopathologic examination stated, that the specimen contained ectopic pancreatic tissue which was involving muscular layer of the ileum. Ectopic pancreatic tissue included acinar cells and cystically dilated secretory ducts without islets of Langerhans. CONCLUSION: Our case report reveals a very rare cause of obscure gastrointestinal bleeding accompanied by the episodes of abdominal pain – an ectopic pancreas located in the ileum.